2022
DOI: 10.1021/acs.jproteome.2c00004
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Identification of Microproteins during the Development of Drosophila melanogaster

Abstract: Short open reading frame-encoded peptides (SEPs) are microproteins with less than 100 amino acids that play an essential role in the growth and development of organisms. There are plenty of short open reading frames in Drosophila melanogaster that potentially code polypeptides. We chose 11 time points during the life cycle of Drosophila to investigate microproteins, particularly those related to development. Finally, we identified a total of 410 microproteins, of which 27 were noncoding RNAencoded proteins. Of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 50 publications
(88 reference statements)
0
5
0
Order By: Relevance
“…The history of high‐throughput identification of SEPs in different species by Ribo‐seq [29, 3471] and MS‐based proteomics [8, 1012, 33, 3856], and representative functional SEPs [5, 14, 16, 1821, 36, 7291]…”
Section: Analysis Strategies and Methodologies Of Sepsmentioning
confidence: 99%
“…The history of high‐throughput identification of SEPs in different species by Ribo‐seq [29, 3471] and MS‐based proteomics [8, 1012, 33, 3856], and representative functional SEPs [5, 14, 16, 1821, 36, 7291]…”
Section: Analysis Strategies and Methodologies Of Sepsmentioning
confidence: 99%
“…The majority of the AltProts identified here are short proteins (88.8% of AltProts are less than 150 amino acids) (Supplementary Figure 1B). Comparing the AltProts identified to the ones with MS evidence in OpenProt and a recent article (Wang et al, 2022), only 2 were common to the three datasets, 29 were found in at least two datasets and 374 new AltProts were identified in this study (Supplementary Figure 1C). The low overlap between the datasets might be explained by the different sample types and extraction and fractionation protocols used (Cardon et al, 2020).…”
Section: Genome Wide Identification Of Alternative Proteins In Drosop...mentioning
confidence: 51%
“…The majority of the AltProts identified here are short proteins (88.8% of AltProts are less than 150 amino acids) (Supplementary Figure S1B). Comparing the AltProts identified to the ones with MS evidence in OpenProt and a recent article (Wang et al, 2022), only two were common to the three datasets, 29 were found in at least two datasets and 374 new AltProts were identified in this study (Supplementary Figure S1C). The low overlap between the datasets might be explained by the different sample types and extraction and fractionation protocols used (Cardon et al, 2020).…”
Section: Genome-wide Identification Of Alternative Proteins In Drosop...mentioning
confidence: 52%